6 - Cameroun : Pourquoi les noms des grandes figures historiques des années 1950 sont-ils tabous dans la bouche du Président Paul Biya ? - Sonne, Soazic Elise Wang (Africa Development, 1997)
Humans are at the beginning and at the end of any past event. Quoting ahistorical fact while leaving aside its authors or heroes is of no interest. The differentspeeches President Biya pronounced in the chief towns of the provinces of Cameroonfrom August to October 1991 are the best illustrations of that. He never mentioned thenames of the figures who were involved in the last fifty years of Cameroon's history. Bethat in ignorance of history or a voluntary omission; such attitudes apart from the Head of Cameroonian State are both instructive enough to deserve a sustained historical study. The author takes his stand on three points: referring to Cameroonian historical figures, the context of the provincial tour and its concrete objective, and the historical nature of the present power. His main finding was the following: to remain as long as possible in power, heirs of the outlaw regime would evade any past event susceptible of concurring them.